Utilization of marigold leaves (Tagetes erecta L.) in rations and their effect on rumen enzyme activity, fermentation parameters, methane emission, and nutrient digestibility in vitro (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study evaluated the utilization of marigold leaves (MGLs) in rations and their impact on rumen enzyme activity, fermentation parameters, methane (CH4 ) emission, and nutrient digestibility in vitro. Materials and Methods: The experimental diets comprised different proportions of MGL incorporated into the dry matter (DM) rations. Experimental design: The MGL treatments in diets include 0% (MGL-0), 7% (MGL-7), and 14% (MGL-14). Results: Results indicated that MGL-14 substantially raised (p < 0.05) the rumen parameters, including NH3 –N and microbial protein, total volatile fatty acids, acetate (C2 ), propionate (C3 ), butyrate (C4 ), and the C2 :C3 ratio. In contrast, the MGL-7 and MGL-14 groups experienced a noteworthy reduction (p < 0.05) in the total protozoa population. The MGL-7 and MGL-14 treatments also led to a substantial increase in the digestibility of DM, organic matter (OM), and crude fiber (CF) in the rumen. However, they also resulted in a decline (p < 0.05) in crude protein (CP) digestibility. The DM and OM total digestibilities were higher (p < 0.05) in the MGL-14 and MGL-7 groups. The utilization of MGL did not influence (p > 0.05) the ruminal enzyme activities (carboxymethyl cellulase, amylase, protease), cumulative gas production, kinetics, ruminal pH value, CH4 and CO2 production, total CF, and CP digestibility. Conclusion: The utilization of MGL until 14% DM in diets can enhance ruminal fermentation parameters and nutrient digestibility in vitro without negatively affecting gas production kinetics or ruminal enzyme activities. However, it did not have any impact on CH4 production.J. Adv. Vet. Anim. Res., 10(4): 782–793, December 2023http://doi.org/10.5455/javar.2023.j734